2022
DOI: 10.1088/1361-6528/aca76f
|View full text |Cite
|
Sign up to set email alerts
|

Load and release of gambogic acid via dual-target ellipsoidal-Fe3O4@SiO2@mSiO2-C18@dopamine hydrochloride -graphene quantum dots-folic acid and its inhibition to VX2 tumor cells

Abstract: Ellipsoidal-Fe3O4@SiO2@mSiO2-C18@dopamine hydrochloride-graphene quantum dots-folic acid (ellipsoidal-HMNPs@PDA-GQDs-FA), a dual-functional drug carrier, was stepwise constructed. The α-Fe2O3 ellipsoidal nanoparticles were prepared by a hydrothermal method, and then coated with SiO2 by Stöber method. The resulting core-shell structure, Fe3O4@SiO2@mSiO2-C18 magnetic nano hollow spheres, abbreviated as HMNPs, was finally grafted with graphene quantum dots (GQDs), dopamine hydrochloride (PDA) and folic acid (FA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Aer loading GA, all results demonstrated that the NPs had acceptable biocompatibility and could be used to treat VX2 tumor cells. 94 Another reported work presented the fabrication of Fe 3 O 4 / hydrophilic mesoporous silica NPs hollow spheres as a drug carrier (HMNPs). Then, polyethyleneimine (PEI) and N-and Sdoped graphene quantum dots (NS-GQDs) were attached to the surface of HMNPs.…”
Section: Inorganic Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Aer loading GA, all results demonstrated that the NPs had acceptable biocompatibility and could be used to treat VX2 tumor cells. 94 Another reported work presented the fabrication of Fe 3 O 4 / hydrophilic mesoporous silica NPs hollow spheres as a drug carrier (HMNPs). Then, polyethyleneimine (PEI) and N-and Sdoped graphene quantum dots (NS-GQDs) were attached to the surface of HMNPs.…”
Section: Inorganic Nanocarriersmentioning
confidence: 99%
“…After loading GA, all results demonstrated that the NPs had acceptable biocompatibility and could be used to treat VX2 tumor cells. 94 …”
Section: Gambogic Acid Nano-delivery Using Nano-particulatesmentioning
confidence: 99%
“…Dong et al constructed a drug carrier by coating ellipsoidal Fe 2 O 3 NPs with SiO 2 and decorated the composite with folic acid, dopamine hydrochloride, and GQDs. The drug carrier was reported to have very low cytotoxicity with high loading and release ability, high lethality towards rabbit squamous cell, and cancer line VX 2 tumor cells after conjugation with gambogic acid (Dong et al, 2023). Magaela et al prepared a PDT platform by linking a tin(IV) porphyrin complex to NGQDs decorated with biotin.…”
Section: Carbon Quantum Dots In Drug Deliverymentioning
confidence: 99%